Portos brasileiros 2009: Ranking, área de influência, porte e valor agregado médio dos produtos movimentados - Carlos Alvares da Silva Campos Neto; Bolívar Pêgo Filho; Alfredo Eric Romminger; Ians\~a Melo Ferreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– Motivated by several factors as the strong growth of Brazilian international commerce, the recover of public and private investments on economic infrastructure, and the good feedback granted by the Texto para Discuss\~ao, n. 1.164 of 2006, we decided to redo that Texto para Discuss\~ao, updating it`s methods and data.The Brazilian international trade has grown 131,7% from 2003 to 2007, going from US 121,4 billions (Free On Board - FOB) to US 281,3 billions (FOB). Than holding to Secex/MDIC 2007's and Rais 2006`s micro-data, we were able to redo the previous study,focusing on the analysis of economic variables which relate to international traded cargos.The importance of this work is also due to the fact that the international commerce made through ports in Brazil has reached approximately US 187,8 billions in 2007, which settles for 76,7% of Brazilian international trade in that year.In order to set a ranking to Brazilian ports, we used six economic variables: a) area influenced by the port (hinterlândia); b) loading capacity (small, medium or large); c) port`s share on Brazilian international trade; d) number of economic sectors - trading sums larger than US 100,0 million - through each port; e) port`s commercial range (national, regional or local); and f) average aggregate value of traded products. First, we generated values out of each variable, than we weighted these values according to their importance for international trading. Finally, the sum of the weighted variables generated a ranking for the ports in focus. We analyzed thirty four ports that deal with international trade in Brazil: Antonina - PR, Aracaju - SE, Aratu - BA, Belém - PA, Corumbá - MS, Fortaleza - CE, Ilhéus - BA, Imbituba - SC, Itajaí - SC, Itaqui - RS, Cabedelo - PB, Macaé - RJ, Macapá - AP, Maceió -AL, Manaus - AM, Munguba - PA, Natal - RN, Niterói - RJ, Paranaguá - PR, Pecém - CE, Porto Alegre - RS, Porto Xavier - RS, Recife - PE, Rio de Janeiro - RJ, Rio Grande - RS, Salvador - BA, Santarém - PA, Santos - SP, S\~ao Francisco do Sul - SC, S\~ao Luís - MA, S\~ao Sebasti\~ao - SP, Itaguaí (Sepetiba) - RJ, Suape - PE, Vitória - ES.
Keywords: L92; H41; F14; 330